ANALISIS PRODUKTIVITAS KERJA GURU WANITA DI SEKOLAH DASAR KECAMATAN SERENGAN SURAKARTA - Eny Kustiyah, Sudarwati , (MAJALAH ILMIAH GEMA, 2014)
The research aims in the long term at investigating and improving theproductivity of work accomplished by elementary female teachers in SerenganSurakarta. It is hopefully enrich the role of woman in academic descipline.Whereas the special target of this research is to improve family’s earning byencouraging woman’s role at home without leaving their rights and nature of awoman. This way is hopefully enrich human resources quality that improveIndonesian development.This research employs survey method; to analyze female elementary teachers’work productivity. Data collecting technique by means of interview; by filling outquestionaries. Purposive random sampling employs in gathering sampling. Thesample in this research are 100 female elementary teachers in 10 elementaryschool of Serengan Surakarta. Data analyzing technique is SPSS version 19.Keywords : The Productivity of Work, Female Elementary Teachers